Software for the frontiers of quantum chemistry: an overview of developments in the Q-Chem 5 package - Epifanovsky, Evgeny; Dempwolff, Adrian; Plasser, Felix; Rehn, Dirk R.; Herbst, Michael F.; Krauter, Caroline M.; Lefrancois, Daniel; Mewes, Jan-Michael; Mewes, Stefanie; Scheurer, Maximilian; Wenzel, Jan; Dreuw, Andreas (The journal of chemical physics, 2021)
This article summarizes technical advances contained in the fifth major release of the Q-Chem quantum chemistry program package, covering developments since 2015. A comprehensive library of exchange-correlation functionals, along with a suite of correlated many-body methods, continues to be a hallmark of the Q-Chem software. The many-body methods include novel variants of both coupled-cluster and configuration-interaction approaches along with methods based on the algebraic diagrammatic construction and variational reduced density-matrix methods. Methods highlighted in Q-Chem 5 include a suite of tools for modeling core-level spectroscopy, methods for describing metastable resonances, methods for computing vibronic spectra, the nuclear-electronic orbital method, and several different energy decomposition analysis techniques. High-performance capabilities including multithreaded parallelism and support for calculations on graphics processing units are described. Q-Chem boasts a community of well over 100 active academic developers, and the continuing evolution of the software is supported by an “open teamware” model and an increasingly modular design.
Gesehen am 19.11.2021